IMPLEMENTASI KEBIJAKAN DAN PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN PELABUHAN KALIWUNGU KABUPATEN KENDAL - Reylea Adrianda Kusuma; edi santosa; puji astuti (Journal of Politic and Government Studies, 2016)
Implementation of the development policy ofKaliwungu port in Kendalarea is a policy made by the Government stated in the local regulation of Kendalarea number 25 of 2007 about the detail layout plan of Kaliwungu port in Kendalarea. From this local regulation, the knowledge of the port construction from thesociety also the purpose and the benefit are absolutely needed. Thus, for thesuccessful development of Kaliwungu port in Kendal area not only depends on therole of the local governments, but it also requires active participations from thelocal society around the site development or Kendal people as a whole.This research is both qualitative and quantitative, with the ultimate goal todescribe thoroughly the implementation of the development policy of Kaliwunguport in Kendal area. The data collection technique used in this study are the indepth interviews, thequestionnaires that is distributed to some respondents (thelocal society in Wonorejo village), the documentations and the analysis ofdocuments. The analysis of documents in this study includes the phase of datareduction, data presentation, and data verification or the conclusion.From the results, it can be concluded that the development policy of Kaliwunguport in Kendal area has been running to its full potential, the Department ofTransportation in Kendal area along with related agencies/SKPD have donestructuring and monitoringof Kaliwungu port in Kendal area with appropriateprocedures, the socialization has also been done by the meeting of coordinationbetween SKPD or directly go to the local society by the related local instruments.Although there are some shortcomings such as the quantity of human resourcesthat needs to be improved and the commitment from the Central Governmentrelated to the operational target of Kaliwungu port. The Local Government inKendal Area must strive to communicate actively with the Central Governmentrelated to the operational permission of Kaliwungu port.